Energy price spread as a driving force for combined generation investments: A view on Europe. (15th November 2016) - Kavvadias, K.C.
Abstract: Combined generation of heat, cooling and power has a large potential to increase its share in distributed generation of energy. Such investments are driven by energy savings which result to operational profits. These profits are very sensitive to the prices of the competitive energy products: electricity and gas. In this work a theoretical indicator is developed between energy prices, the technical characteristics of cogeneration and conventional generation equipment and the investment viability. Through this indicator, the operational profitability of cogeneration equipment is mapped and discussed. Empirical rules are extracted which can give a clear view of the sensitivity of energy prices on energy efficiency investments. The European cogeneration status quo is analyzed in terms of energy prices and market share. The developed indicator is also used, to analyze market related barriers and highlight the importance of energy pricing policy as a tool to minimize the risk exposure of energy efficiency investments. Highlights: Energy price spread of competitive fuels affects combined generation profitability. Its uncertainty is the most important barrier for new investments. The minimum energy price spread had been generalized and mathematically justified. Can be used as a tax-based mechanism to hedge the risk of fuel price fluctuations. For a typical installation, power has to be at least 2 times more expensive than gas.